The biomechanics of race walking: Literature overview and new insights - Pavei, G.; Cazzola, D.; La Torre, A.; Minetti, A. E. (European Journal of Sport Science, 2014)
This review aims to provide both researchers and coaches with a comprehensive overview of race walking biomechanics and to point out new viable route for future analyses. The examined literature has been divided into three categories according to the method of analysis: kinematics, ground reaction forces and joint power/efficiency. From an overall view, race walking athletes seem to adhere to the `straightened knee` rule, but at race speed they do not observe the `no-flight time` rule. The coach-oriented analysis highlights that stride length (SL) is more important than stride frequency (SF) for increasing speed and it is mainly obtained by ankle and hip joint power. Moreover, kinematic differences (SF, SL and flight time) between male and female athletes were shown. Also, we found that the maximal speed prediction according to dynamic similarity theory with walking (Froude number) is not applicable as the 3D trajectory of the body centre of mass does not follow an arc of circumference as in walking. The analysed literature shows some shortcomings: (1) the data collection is often unreliable because of the mixture of gender and performance level and (2) the analysis has sometimes been performed on a limited number of strides and speeds. These limitations lead to a scattered and incomplete gait description and a biased application of the results. The research strategy adopted so far is promising but further rigorous analyses need to be approached to obtain a fully comprehensive picture of race walking and to provide coaches with consistent results and reference values.